AB1257 Assessing MRI erosions in the rheumatoid wrist: A comparison between RAMRIS and a semiautomated segmentation software. (23rd January 2014) - Barbieri, F.; Parascandolo, P.; Vosilla, L.; Cesario, L.; Viano, G.; Cimmino, M.A.
Abstract : Background: Bone erosions have been always considered the hallmark of rheumatoid arthritis (RA). Advanced imaging techniques, such as computed tomography, MRI, and, at least in several joint areas, ultrasonography have shown increased sensitivity for demonstration of erosions in comparison with conventional radiography. In addition, modern follow-up of erosions requires high sensitivity to change in view of the increased capability of new therapeutic strategies to promote their healing. In MRI, the RAMRIS erosion score is used to subjectively estimate the volume of erosions on a scale comprised between 0 and 10, based on the percentage of eroded bone. This method is time consuming and not fully repeatable, especially for unexperienced readers. An automated software able to calculate the volume of the erosions could improve imaging follow up of RA patients. Objectives: To calculate the volume of the erosions located in bones of the wrist and of the metacarpal bases by a semiautomated software. To compare the results with those obtained by the RAMRIS method. Methods: 26 patients (21 women) diagnosed with early RA according to the 1987 ACR criteria were studied. The wrists were imaged through an extremity-dedicated MRI device (Artoscan C, Esaote, Genova Italy). A turbo T1-weighted three dimensional sequence (T3-D T1) in the coronal plane, with subsequent multiplanar reconstructions on the axial and sagittal planes was used; slice thickness was 0, 3 mm, TR 860 ms, TE 26 ms, and number of excitations (NEX) 1. An experimental software for the segmentation of the bones of the wrist (RHEUMAScore, Softeco Sismat SrL, Genova, Italy) was used. After wrist bones and metacarpal bases segmentation through an algorithm, the resulting outline was adjusted manually using a tool editing 2D, when necessary. Tridimensional reconstruction and volumes assessment was performed. The software is able to identify and measure bone erosions, defined as missing volume of substance compared to an average statistical model built on bones of healthy subjects. The operator can confirm the automatic evaluation of erosions or modify it by removing the areas incorrectly diagnosed. The system then assigns a score to the erosions with a similar mechanism to that of RAMRIS. Results: The median erosion scores revealed by the RAMRIS method and the new software were 2 (range 0-26) and 2 (range 0-21), respectively. The two scores were correlated (correlation coefficient 0.9, p<0.0001). Weighted k was 0.706 for the entire score and was comprised between 0.264 and 0.887 for the individual bones. The poorest result was seen for the scaphoid due to underestimation of a relatively large erosion (RAMRIS score 3) because of the very large size of the wrist bones of this patient. Conclusions: This semiautomated segmentation software showed a good correlation with the RAMRIS erosion score. Further refinements are necessary to obtain a fully automated version which could be used in follow-up studies. Disclosure of Interest: F. Barbieri: None Declared, P. Parascandolo Employee of: Softeco Sismat SrL, L. Vosilla Employee of: Softeco Sismat SrL, L. Cesario Employee of: Softeco Sismat SrL, G. Viano Employee of: Softeco Sismat SrL, M. Cimmino: None Declared